Waste and well-being: Examining waste management challenges and disease burden among marginalized populations in Ghana - Kwame Anokye; Abigail Okyere Darko; Portia Agyemang; Luther Kwabi Adjei; Mary Wejaamo Ayeriga; Douti Nang Biyogue; Ebenezer Ebo Yahans Amuah; Bosompem Ahunoabobirim Agya; Stephen Sodoke; Awal Ahmed Mohammed (Social Sciences and Humanities Open)
Inadequate solid waste management (SWM) systems remain a pressing public health and environmental challenge, particularly in low- and middle-income countries. This study conducts a thematic, interdisciplinary review of household, healthcare, and electronic waste management practices in Ghana, with a specific focus on their health and socio-economic impacts on marginalized communities. Drawing on academic literature, policy documents, and institutional reports, the study critically examines existing governance structures and evaluates the relevance of circular economy (CE) principles to the Ghanaian context. Findings reveal persistent exposure to waste-borne diseases, weak policy enforcement, limited stakeholder coordination, and systemic marginalization of vulnerable populations in SWM planning and implementation. The review identifies significant gaps in waste data, institutional accountability, and sustainable infrastructure. Notably, it highlights how CE strategies—if localised and inclusive—can provide innovative pathways for sustainable and equitable waste solutions. This study offers novel insights by integrating perspectives on health equity, governance, and CE into a unified analysis of waste systems. While grounded in Ghana, the findings offer broader implications for other Global South contexts seeking to transition toward sustainable and inclusive waste management frameworks.